Outbreaks of Foot‐and‐Mouth Disease in Libya and Saudi Arabia During 2013 Due to an Exotic O/ME‐SA/Ind‐2001 Lineage Virus. Issue 5 (7th December 2014) - Knowles, N. J.; Bachanek‐Bankowska, K.; Wadsworth, J.; Mioulet, V.; Valdazo‐González, B.; Eldaghayes, I. M.; Dayhum, A. S.; Kammon, A. M.; Sharif, M. A.; Waight, S.; Shamia, A. M.; Tenzin, S.; et al.
Summary: Foot‐and‐mouth disease viruses are often restricted to specific geographical regions and spread to new areas may lead to significant epidemics. Phylogenetic analysis of sequences of the VP1 genome region of recent outbreak viruses from Libya and Saudi Arabia has revealed a lineage, O‐Ind‐2001, normally found in the Indian subcontinent. This paper describes the characterization of field viruses collected from these cases and provides information about a new real‐time RT‐PCR assay that can be used to detect viruses from this lineage and discriminate them from other endemic FMD viruses that are co‐circulating in North Africa and western Eurasia.